Znaczenie przywództwa jako wartości niematerialnej w kształtowaniu wartości przedsiębiorstwa - Skowron, Paweł (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Not material value is called leadership. It is one of the most precious assets of a company. Economics of immaterial value shows that somebody who runs a company is responsible for creating the image of the brand, making organisation's culture. He is a factor of value creation. On the other hand - all the people who are interested in a company for example: investors, suppliers, competitors and workers, who will work there in the future are all associated with the company and estimate its potential. Well-running company, developing subordinates's skills, creating co-operation's culture, workers's fluctuacion or satisfaction becomes the measure of company's estimation. The people will feel associated with the company and will stay there as long as the company's management system will give them satisfaction with their job. All of these elements influence company's price on the market. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 134-140